TRIAMF: A New Method for Delivery of Cas9 Ribonucleoprotein Complex to Human Hematopoietic Stem Cells. Issue 1 (December 2018) - Yen, Jonathan; Fiorino, Michael; Liu, Yi; Paula, Steve; Clarkson, Scott; Quinn, Lisa; Tschantz, William; Klock, Heath; Guo, Ning; Russ, Carsten; Yu, Vionnie; Mickanin, Craig; et al.
Abstract CRISPR/Cas9 mediated gene editing of patient-derived hematopoietic stem and progenitor cells (HSPCs)ex vivo followed by autologous transplantation of the edited HSPCs back to the patient can provide a potential cure for monogenic blood disorders such as β-hemoglobinopathies. One challenge for this strategy is efficient delivery of the ribonucleoprotein (RNP) complex, consisting of purified Cas9 protein and guide RNA, into HSPCs. Because β-hemoglobinopathies are most prevalent in developing countries, it is desirable to have a reliable, efficient, easy-to-use and cost effective delivery method. With this goal in mind, we developed TRansmembrane Internalization Assisted by Membrane Filtration (TRIAMF), a new method to quickly and effectively deliver RNPs into HSPCs by passing a RNP and cell mixture through a filter membrane. We achieved robust gene editing in HSPCs using TRIAMF and demonstrated that the multilineage colony forming capacities and the competence for engraftment in immunocompromised mice of HSPCs were preserved post TRIAMF treatment. TRIAMF is a custom designed system using inexpensive components and has the capacity to process HSPCs at clinical scale.